Molecular Mechanisms of Plant Stress Memory: Roles of Non-Coding RNAs and Alternative Splicing - Mariz Sintaha (Plants, 2025)
The ability of plants to protect themselves from stress-related damages is termed “adaptability” and the phenomenon of showing better performance in subsequent stress is termed “stress memory”. This phenomenon has been reported in various stresses such as drought, heat, salinity, cold, and heavy metal toxicity. Histone modification leading to chromatin remodeling and accumulation of phosphorylated RNA polymerase on the promoters of memory genes is a well-known mechanism of plant stress memory. Recent studies have revealed the role of non-coding RNAs (ncRNAs) and alternative splicing (AS) in memory-specific gene expression and transgenerational inheritance of stress memory. MicroRNAs (miRNAs) inhibit specific genes to enable plants to respond better in subsequent drought and heat stress, while long non-coding RNAs (lncRNAs) play roles in epigenetic regulation of memory gene expression in cold and salt stress. Small interfering RNAs (siRNAs) lead to DNA methylation during the memory response of biotic, salt, and heavy metal stress. Simultaneously, stress-responsive isoforms of tolerant genes are found to be expressed as a memory response in subsequent heat stress. This review highlights the stress-type-specific roles of ncRNAs and AS in establishing, maintaining, and transmitting stress memory, offering insights into their potential for improving crop resilience through genetic and epigenetic priming strategies.